2015
DOI: 10.1590/0103-8478cr20140333
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização dos acidentes com máquinas agrícolas em rodovias federais no estado do Rio Grande do Sul

Abstract: Caracterização dos acidentes com máquinas agrícolas em rodovias federais no estado do Rio Grande do Sul.Ciência Rural, v.45, n.1, jan, 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
0
3
0
5
Order By: Relevance
“…Additionally, is important to highlight the accidents majority happened in daytime period, bearing in mind in Brazil the sun rises at 6a.m and sets at 6 pm, which has not influenced operator's visibility. Macedo (2015) argues that the bulk of incidents' events happen in both the afternoon and the morning, in this sequence, highlighting the crashes that happen when the operators' shift is almost finished, event usually due tiredness. The weather conditions at the moment the episode happened is illustrated in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, is important to highlight the accidents majority happened in daytime period, bearing in mind in Brazil the sun rises at 6a.m and sets at 6 pm, which has not influenced operator's visibility. Macedo (2015) argues that the bulk of incidents' events happen in both the afternoon and the morning, in this sequence, highlighting the crashes that happen when the operators' shift is almost finished, event usually due tiredness. The weather conditions at the moment the episode happened is illustrated in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…Apesar de concebidos como força de trabalho e projetados para a operação em atividades agrícolas, essas máquinas necessitam realizar deslocamentos de uma área para outra, fazendo o uso não só de estradas da propriedade, como também de vias públicas [7][8][9][10][11][12][13]. Entretanto, quando os tratores agrícolas trafegam nessas vias, caracterizam-se como veículos lentos por trafegarem, geralmente, a uma velocidade entre 15 km.h -1 e 20 km.h -1 , muito inferior à velocidade atingida por outros veículos [9]. No Brasil, onde não existe sinalização regulamentadora, a velocidade máxima das vias urbanas varia de 30 km.h-1, em vias locais; a 80 km.h-1, em vias de trânsito rápido.…”
Section: Introductionunclassified
“…The agricultural tractor is the most important source of power in the agricultural environment, contributing to the development and technological advancement of the Agricultural Production Systems (APS), as the only way to guarantee the gains of scale that are observed in the global Agribusiness. However, the tractor is also a source of risk of accidents and injuries to workers (Schlosser et al, 2002, Hoy, 2009, Macedo et al, 2015, Casazza et al, 2016, Lleras et al, 2016. Springfeldt (1996) and Khorsandi et al 2017 reported that within accidents involving agricultural tractors the primary cause is tractor rollover, Murphy & Yoder (1998) mention that rollover accounts for a third of total fatalities involving agricultural workers.…”
Section: Introductionmentioning
confidence: 99%